2020
DOI: 10.1038/s41598-020-71731-2
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparative analysis of choledochoscopic bile duct exploration versus ERCP for bile duct stones

Abstract: Debate still exists for the management of choledocholithiasis. The purpose of this study is to quantify the rate of recurrent choledocholithiasis post choledochoscopic bile duct exploration (CBDE) in comparison to ERCP and sphincterotomy, and to demonstrate the feasibility of this approach in a busy metropolitan hospital. Data of patients undergoing CBDE from 2009–2014 at the Northern Hospital, Victoria, Australia, was collected retrospectively. Primary outcomes were bile duct clearance rate and rate of recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…(68) Some retrospective comparative analyses and meta-analyses showed that the rate of recurrence was lower in the LCBDE group compared to the patients who had an EST. (3,63) LC+LCBDE preserve the complete sphincter function of Oddi, which may be associated with the reduction of the recurrence rate of common bile duct stones. A larger sample size should be studied to clarify this conclusion.…”
Section: Endoscopic Nasobiliary Drainage (Enbd) and Saline Preventivementioning
confidence: 99%
“…(68) Some retrospective comparative analyses and meta-analyses showed that the rate of recurrence was lower in the LCBDE group compared to the patients who had an EST. (3,63) LC+LCBDE preserve the complete sphincter function of Oddi, which may be associated with the reduction of the recurrence rate of common bile duct stones. A larger sample size should be studied to clarify this conclusion.…”
Section: Endoscopic Nasobiliary Drainage (Enbd) and Saline Preventivementioning
confidence: 99%
“…Los estudios de Al-Habbal, et al y Al-Temimi et al reportaron una baja incidencia de pacientes que ameritaron CPRE postoperatoria por litiasis residual. (14,17) Pan, et al reportan una tasa de eliminación de litiasis coledociana de 94,1% en el grupo laparoscópico vs. 90,1% en el grupo de CPRE preoperatoria con diferencia estadísticamente significativa. La tasa de litiasis residual fue 1,2 vs 7,9% para los pacientes con exploración laparoscópica de la vía biliar y CPRE preoperatoria respectivamente; resultados estos similares a los obtenidos en el meta-análisis de Zhu et al (9,18) Los resultados de nuestro estudio no lograron demostrar una superioridad evidente del abordaje laparoscópico sobre el convencional, sin embargo no podemos desestimar las ventajas que ofrece la cirugía laparoscopia sobre el abordaje convencional en términos de menor trauma quirúrgico, menor dolor postoperatorio, menor tiempo de hospitalización y una reincorporación más rápida a las actividades habituales del paciente.…”
Section: Discussionunclassified
“…and it has been documented that stone recurrence after ERCP was higher compared with choledoscopic bile duct exploration 16 . Other late sequelae of ERCP include papillary stenosis that may further predispose to cholangitis and pancreatitis 17,18 and post‐sphincterotomy duodenal reflux has also been reported to be a risk factor for cholangiocarcinoma 19,20 . A definite advantage of LTCE is that the sphincter of Oddi is preserved.…”
Section: Discussionmentioning
confidence: 99%